Dikotomi Pendidikan Sekolah dan Madrasah: Tantangan, Realitas, dan Solusi dalam Mencapai Pendidikan Inklusif - Baron Santoso; Sukari Sukari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the differences between schools and madrasahs, the impacts they cause, and the efforts needed to make education more inclusive and equitable. In Indonesia, the education system is divided into two large institutions, namely public schools and madrasahs. This study uses a qualitative descriptive approach to analyze the dichotomy between schools and madrasahs. The results of the study are that differences in curriculum, facilities, and public perceptions create gaps in the quality of education. Therefore, efforts to integrate the curriculum and improve madrasah facilities need to be made. A more inclusive education system can be realized through steps such as integrating the curriculum between madrasahs and public schools, increasing the allocation of funds and madrasah facilities, eliminating negative stereotypes through inclusive public campaigns. Further research can be conducted using field methods to understand the conditions of madrasahs in more depth.